Cystic Teratoma of the oral cavity - Farahnaz Bidari Zerehpoosh; Mahdi Khajavi; Mahnaz Baradaran; Mansoureh Baradaran (Elsevier, 2022)
We present a rare case of sublingual cystic teratoma in the oral cavity with atypical magnetic resonance imaging (MRI) findings in a 4-year-old girl. The MRI demonstrated a well-marginated lesion in the oral cavity floor, high signal on T2-and iso signal on T1-weighted with thick wall and wall enhancement after intravenous contrast injection. The MRI findings were related to a congenital cyst of the oral cavity with a high proteinaceous material, suggesting an infected ranula. The cyst was surgically removed. The histopathological section of the excised specimen demonstrated a cyst line by epidermoid stratified squamous epithelium and ciliated respiratory mucosa, compatible with maturing cystic teratoma.